Cultivating Peace : Conflict and Collaboration in Natural Resource Management - Buckles, Daniel, 1955- (International Development Research Center, 1999)
Whether it be a local dispute between farmers and ranchers or an international clash over shared resources, people everywhere compete for the natural resources they need to ensure or enhance their quality of life. While the dimensions, levels, and intensity of conflict can vary greatly, so too can the opportunities for conflict resolution. This book presents original case studies from Africa, Asia, and Latin America, interspersed with essays on the cultural dimensions of conflict, the meaning of stakeholder analysis, the impact of development interventions on peace and conflict, and the policy dimensions of conflict management. The case studies present developing-world experience on moving from conflict to collaborative modes of management. The accompanying essays draw on the case studies, grounding theory in hard-won experience.--Publisher's description.